2000
DOI: 10.1089/thy.2000.10.587
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Anaplastic Thyroid Carcinoma with Paclitaxel: Phase 2 Trial Using Ninety-Six-hour Infusion

Abstract: Anaplastic thyroid carcinoma is a rare, lethal disease with no effective systemic therapies. Preclinical studies demonstrated antineoplastic activity of paclitaxel. This prompted a prospective phase 2 clinical trial to determine activity of paclitaxel against anaplastic thyroid carcinoma in patients with persistent or metastatic disease despite surgery or local radiation therapy. Twenty patients, entered through 6 of 12 study sites, were treated with 96-hour continuous infusion paclitaxel every 3 weeks for 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(170 citation statements)
references
References 34 publications
7
157
0
5
Order By: Relevance
“…Paclitaxel has demonstrated prolongation of life for ATC patients in a clinical trial and appears the standard of care with regards to chemotherapeutic intervention for patients diagnosed with ATC (Ain et al, 2000). Aldred et al (2003) described PPARg expression in thyroid cancer subtypes demonstrating that ATCs were positive by IHC in 9/14 cases and percentage-wise, PPARg expression was higher than any other thyroid cancer subtype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paclitaxel has demonstrated prolongation of life for ATC patients in a clinical trial and appears the standard of care with regards to chemotherapeutic intervention for patients diagnosed with ATC (Ain et al, 2000). Aldred et al (2003) described PPARg expression in thyroid cancer subtypes demonstrating that ATCs were positive by IHC in 9/14 cases and percentage-wise, PPARg expression was higher than any other thyroid cancer subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this is based upon a recent report demonstrating that p21 WAF1/CIP1 enhanced apoptosis induced by manumycin and paclitaxel in ATC cells (Yang et al, 2003) along with the efficacy demonstrated for paclitaxel in a clinical trial of ATC patients (Ain et al, 2000). We reasoned that RS5444 strongly upregulated p21 WAF1/CIP1 and that increased p21 WAF1/CIP1 may lead to enhanced antitumor activity in the presence of paclitaxel.…”
Section: Rs5444 Induces Cyclin Kinase Inhibitors (Cki) In Atc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of combination chemotherapy show no increased response over single agent doxorubicin and increased toxicity (292). Some specialists recommend consideration of single agent doxorubicin or paclitaxel, or a combination of these agents based on limited data in anaplastic thyroid carcinoma (293). One recent study evaluated the effect of combination chemotherapy (carboplatinum and epirubicin) under TSH stimulation (endogenous or rhTSH) (294), demonstrating an overall rate of complete and partial response of 37%.…”
Section: What Is the Role Of External Beam Radiotherapy In Treatment mentioning
confidence: 99%
“…This carcinoma is highly malignant, nonencapsulated, extends widely, and has a poor prognosis [6][7][8][9][10][11]. In several anaplastic thyroid carcinoma cell lines, many cytokines such as granulocyte-colony stimulating factor (G-CSF), granulocyte macrophage-colony stimulating factor (GM-CSF), IL-1a, IL-6, and TGF-a are produced [12][13][14][15].…”
mentioning
confidence: 99%